2015
DOI: 10.1039/c5ra07783d
|View full text |Cite
|
Sign up to set email alerts
|

A unified approach toward the rational design of selective low nanomolar human neutrophil elastase inhibitors

Abstract: A computer-aided campaign boosted the discovery of potent human neutrophil elastase (HNE) inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…A very interesting group of compounds that caught our attention are azetidine-2,4-diones, also known as 4-oxo-β-lactams [ 26 ]. These compounds showed the ability to serine acylation in HNE, and further research on the structure optimization showed that N -phenyl derivatives of 3,3-diethylazetidine-2,4-dione G ( Figure 1 ) show much higher activity and selectivity towards HNE [ 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…A very interesting group of compounds that caught our attention are azetidine-2,4-diones, also known as 4-oxo-β-lactams [ 26 ]. These compounds showed the ability to serine acylation in HNE, and further research on the structure optimization showed that N -phenyl derivatives of 3,3-diethylazetidine-2,4-dione G ( Figure 1 ) show much higher activity and selectivity towards HNE [ 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%